A rare presentation of an open traumatic scapulothoracic dissociation following conveyor machine hazard - Sharifudin, Mohd Ariff; Ismail Mansor, Nur Akmal; Che Ahmad, Aminudin; Awang, Mohd Shukrimi; Mohamed Amin, Mohamed Azril; Zakaria@Mohamad, Zamzuri; Awang, Ahmad Khadri; Taib, Mai Nurul Ashikin (2014)
Introduction: Scapulothoracic dissociation refers to the high-force traumatic injury causing complete or partial separation of the shoulder girdle from the lateral thoracic wall. Commonly observed mode of injury is a massive traction force applied to the upper extremity. In any scapulothoracic dissociation, scapular displacement is accompanied by significant soft tissue injuries. Classically, the injuries invariably present with an intact overlying skin and is commonly referred to as closed forequarter amputation. Immediate vascular control is essential but difficult due to the concealed, active bleeding. Case Report: We present a rare case of an open traumatic scapulothoracic dissociation following an industrial mishap. A 16-year-old male Orang Asli had his hand trapped in a conveyer belt during work. He uses his body weight to apply lateral traction force to release his hand. This caused his whole upper extremity avulsed totally at the level of scapulothoracic and acromioclavicular articulation. Surprisingly, his hand and forearm were not seriously mutilated, as what usually observed in such occupational hazards. Resuscitation was not a troublesome as overt bleedings were easily identified and secured. The patient was managed by aggressive debridements with ligation of the neurovascular stumps on the first surgery. The avulsed upper extremity was not salvageable in view of the magnitude of the injuries. Conclusion: The purpose of this case report is to bring in notice this rare entity and to redefine the injury. The most logical mechanism to explain such event is the massive lateral traction with the body weight of the patient in an outstretched upper extremity. The muscles of the upper extremity might be in a stretched state leading to overload tension onto the scapulothoracic and acriomioclavicular articulation.